Estimation of the National Income Function (United States and China): A Comparative Study for the Period (2000-2019) - Al-Khafaji, Loma Abbas (Research Parks Publishers, 2024)
The research aims to analyze the national income function of the United States and China, considering them the most influential countries in the trade system. It also analyzes the factors behind the development of the Chinese economy over the past few decades. A time series of national income variables for both countries, spanning from 2000 to 2019, was reviewed. The researchers constructed a linear model to estimate both functions using the linear model. The research concluded that China's commercial dominance on the international stage is the result of several factors, including China's implementation of a planned market economy that combines the advantages of capitalism and socialism, as well as the Chinese government's complete control over economic management. Additionally, the flexibility of China's production system and its response to the devaluation of the local currency, the yuan, played a role. However, despite this, the dominance of the U.S. economy in international economic activity remains paramount due to the vast scale of economic operations and activities conducted by the United States.